2018
DOI: 10.4204/eptcs.279.4
|View full text |Cite
|
Sign up to set email alerts
|

Global Types for Open Systems

Abstract: Global-type formalisms enable to describe the overall behaviour of distributed systems and at the same time to enforce safety properties for communications between system components. Our goal is that of amending a weakness of such formalisms: the difficulty in describing open systems, i.e. systems which can be connected and interact with other open systems. We parametrically extend, with the notion of interface role and interface connection, the syntax of global-type formalisms. Semantically, global types with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 18 publications
0
48
0
Order By: Relevance
“…Instead in the present paper we can use the standard syntax to build the global type of the session obtained by connecting. Moreover, we have shown that the compatibility relation of [1], which requires duality, can be relaxed to a relation strongly similar to session-types' subtyping [14,11]. Our structural preorder on processes mimics the subtyping relation between session types of [7], which is a restriction of the subtyping of [11].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead in the present paper we can use the standard syntax to build the global type of the session obtained by connecting. Moreover, we have shown that the compatibility relation of [1], which requires duality, can be relaxed to a relation strongly similar to session-types' subtyping [14,11]. Our structural preorder on processes mimics the subtyping relation between session types of [7], which is a restriction of the subtyping of [11].…”
Section: Related Workmentioning
confidence: 99%
“…In the present paper we have provided a multiparty formalism and we have adapted the approach of [1] to it. Our calculus of multiparty sessions is like those of [12,15], but for the use of coinduction instead of induction which is inspired by [6,27].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations